A facile "turn-on" fluorescent aptasensor for simultaneous detection of dual mycotoxins in traditional Chinese medicine based on graphene oxide and FRET. (30th January 2022) - Zhang, Nan; Li, Jingrong; Liu, Boshi; Wang, Haixia; Zhang, Di; Li, Zheng
Abstract: Mycotoxin is a common sort of harmful contaminant in traditional Chinese medicine (TCM), which is in a great demand of controlling. On this account, a facile "turn-on" fluorescent aptasensor based on fluorescence resonance energy transfer (FRET) for simultaneous detection of patulin (PAT) and zearalenone (ZEN) was developed. In this study, the aptamers of PAT and ZEN were labeled by FAM and Cy3, respectively, serving as fluorescence probes. Both aptamers could adsorb on the surface of graphene oxide (GO) via π-π stacking, which will consequently result in the occurrence of FRET between the fluorophores and GO. In the absence of the targets, the fluorescence would be quenched "off". In the presence of any of the dual mycotoxins, the corresponding aptamers would interact with the targets and release from GO due to the conformational variation, leading to a fluorescence "turn-on" effect. The limit of detection of this difunctional aptasensor was 2.29 nM for PAT and 0.037 nM for ZEN, respectively. This aptasensing platform exhibited satisfactory selectivity against interferents and reliability in real TCM sample detection. To our knowledge, it is the first aptasensor based on GO and FRET that realizes simultaneous detection of dual mycotoxin in TCM. Moreover, the measurement takes merely ∼60 min, does not need complicated pretreatment, and uses only inexpensive aptamer and GO as consuming materials. To sum up, this aptasensor exhibits great potential in fast, cost-effective and reliable simultaneous detection of multiple targets, and is expected to contribute to the quality and safety control of TCM. Graphical abstract: Image 1 Highlights: A facile aptasensor for simultaneous detection of dual mycotoxins in traditional Chinese medicine was developed. This aptasensor performed satisfactory sensitivity and selectivity toward patulin and zearalenone. This aptasensor exhibited simple, fast detection and great potential in simultaneous detection of multiple targets. Graphene oxide and fluorescence resonance energy transfer were first applied in traditional Chinese medicine assay. Low-priced aptamer and graphene oxide were the only consuming materials and helped to realize cost-effective detection.